The utility of clinical ultrasonography in identifying distal forearm fractures in the pediatric emergency department. (April 2019) - Galletebeitia Laka, Iratxe; Samson, Frederic; Gorostiza, Inigo; Gonzalez, Andrés; Gonzalez, Carlos
Abstract : Objective: The aim of this study is to evaluate the utility of Point-Of-Care Ultrasound (POCUS) for diagnosing distal forearm fractures in pediatric emergency departments (ED). Patients and methods: A prospective observational study was carried out in children aged younger than 15 years attended in an ED with an indication of radiography because of a suspected distal forearm fracture. The POCUS was performed considering cortical irregularity or disruption compatible with fracture. Then, the radiography was requested and the patient was evaluated by an ED traumatologist. Both tests were blinded to each other. The radiograph was considered to be the reference diagnostic test. Diagnostic validation tests were performed. Results: A total of 115 patients [mean age: 9.1 (SD: 3.1) years; 50.4% males] were included, with 57 of these presenting fractures: 42 (73.7%) single bone fractures and 15 (26.3%) combined fractures of the radius and ulna. As such, 72 fractures were detected (prevalence 31.3%). The sensitivity and specificity of POCUS for detecting fractures were 94.4% [95% confidence interval (CI): 86.4–98.5] and 96.8% (95% CI: 92.8–99.0), respectively. The positive and negative predictive values were 93.2% (95% CI: 84.7–97.7) and 97.5% (95% CI: 93.6–99.3), respectively. Conclusion: POCUS enables the clinical diagnosis of distal forearm fractures in ED. In addition, this is a highly accurate technique that can be applied easily by the ED pediatrician. As such, its inclusion as part of the physical examination could improve the accuracy of the clinical diagnosis and the global management of the patient.